Strategi Peningkatan Efektivitas Keputusan Pembelian Konsumen terhadap Produk Ramah Lingkungan Air Mineral “Aqua Life” - Wijaya, Pang Kie; Wardhana, Ali (Journal of Business & Applied Management, 2023)
Consumer buying decisions are part of consumer behavior, namely the study of how individuals, groups, and organizations choose, buy, use, and how goods, services, ideas or experiences to satisfy their needs and desires. Purchasing decisions, namely consumers have a choice before taking action in buying an item or service. In other words, consumers who will make a choice must make a choice from various alternatives. This study aims to determine and analyze the effect of price, environmentally friendly marketing, and environmental awareness on purchasing decisions in the bottled drinking water industry, namely aqua life mineral water. The population in this study were all consumers who had purchased Aqua Life mineral water products. The data obtained were primary data. This sampling method is atechnique non-probabilty sampling and obtains a sample of 106 respondents. This type of research is quantitative using descriptive statistical methods. The analysis in this study uses theSmartPLS 3.0 program to analyze and test the data. Based on the results of the research conducted, the conclusions obtained are that price, environmentally friendly marketing and environmental awareness have a significant effect on purchasing decisions. The results of this study support research that has been carried out by previous researchers